2018
DOI: 10.1111/hiv.12639
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to antiretroviral drugs and the incidence of hypertension in HIV‐positive persons: the Data Collection on Adverse Events of Anti‐HIV Drugs (D:A:D) study

Abstract: We did not find evidence for any strong independent association between exposure to any of the individual ARV drugs and the risk of hypertension. Findings provide reassurance that screening policies and preventative measures for hypertension in HIV-positive persons should follow algorithms used for the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
38
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 41 publications
13
38
3
2
Order By: Relevance
“…Higher BMI was found to be associated with an increased risk of prevalent hypertension in our patients. is finding was in agreement with the study from the country [23] and other studies elsewhere [15,27,31,35], indicating that HIVinfected patients classified as overweight or obese were at an increased risk of developing hypertension. Our study also found a significant association between the presence of diabetes and prevalence of hypertension.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Higher BMI was found to be associated with an increased risk of prevalent hypertension in our patients. is finding was in agreement with the study from the country [23] and other studies elsewhere [15,27,31,35], indicating that HIVinfected patients classified as overweight or obese were at an increased risk of developing hypertension. Our study also found a significant association between the presence of diabetes and prevalence of hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…e increased risk of hypertension observed among older HIV-infected patients on ART in our study is consistent with previous studies [14,24,27,31,34]. ese and other related studies [15,35] showed that older patients had an increased risk of prevalent hypertension and should be targeted for frequent blood pressure monitoring and the identification of other risk factors to encourage lifestyle modification. We also observed a significant association between male gender and hypertension in our study population, and this was in agreement with previous reports [15,34,35], which indicated that male patients were at an increased risk of hypertension during their time on ART.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations